Game Theoretical Analysis of Corruption on the Road in Indonesia - Ibnu Abbas, Muhammad Hasyim; Maytandi, Andre (KnE Social Sciences, 2020)
This paper aims to analyze the empirical mechanism of the bribery and extortion on the roads in Indonesia. Using a game theoretical approach, the game is played by two representative agents, namely Police and Rider. The mechanism is modeled into two stage games. Stage 1 adopts the 2x2 simultaneous Tsebelis’ inspection game refined by Pradiptyo. Stage 2 illustrates two scenarios of sequential game. Stage 1 proposes that the benefit of enforcing the law gained by the police becomes rider’s important consideration to violate the traffic laws and rules while stage 2 proposes that the benefit of enforcing laws and rules is the important point to avoid bribery. Stage 2 also suggests that the law enforcement institutions may think carefully before increasing the severity of penalties and sanctions suffered by riders because it would increase the likelihood of police to extort the riders. Keywords: Bribery, Extortion, Game Theory, Inspection Game